2011
DOI: 10.1103/physrevb.83.075201
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a silicon-related defect detected by its excited triplet state in electron-irradiated 3C-SiC

Abstract: Using electron paramagnetic resonance (EPR) under band-gap illumination, we show experimental evidence of a defect center in n-type cubic silicon carbide (3C-SiC) single crystal irradiated with 1-MeV electrons. This defect is diamagnetic (S = 0) in its ground state and can be pumped into a paramagnetic (S = 1, M S = 0) state by above-band-gap photon excitation, where it is detected by EPR absorption and emission transitions M S = 0 ↔ M S = ± 1. This defect is characterized by g = 2.0029, a zero-field splitting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 43 publications
3
6
0
Order By: Relevance
“…As the same with previous results with DFT-LDA, 73 it is shown in both PBE and HSE0.15 results that the mixed spin state of singlet would be the ground state rather than the spin triplet state in V Si 0 , which agrees with an electron paramagnetic resonance (EPR) experimental result. 74 The result that a high spin state (S = 3/2) is more stable than a low spin state (S = 1/2) for V Si 1− also agrees with an EPR experimental result 75 and a previous DFT-LDA result. 76 However, for V Si 0 , the spin triplet state is just 0.07 eV less stable than the singlet mixed-spin state in HSE0.15 description (0.22 eV less stable in PBE description).…”
Section: B Silicon Vacancy-type Defectssupporting
confidence: 79%
See 1 more Smart Citation
“…As the same with previous results with DFT-LDA, 73 it is shown in both PBE and HSE0.15 results that the mixed spin state of singlet would be the ground state rather than the spin triplet state in V Si 0 , which agrees with an electron paramagnetic resonance (EPR) experimental result. 74 The result that a high spin state (S = 3/2) is more stable than a low spin state (S = 1/2) for V Si 1− also agrees with an EPR experimental result 75 and a previous DFT-LDA result. 76 However, for V Si 0 , the spin triplet state is just 0.07 eV less stable than the singlet mixed-spin state in HSE0.15 description (0.22 eV less stable in PBE description).…”
Section: B Silicon Vacancy-type Defectssupporting
confidence: 79%
“…An EPR experiment supports the emergence of the V Si 0 state in 3C-SiC, which was detected after 1 MeV electron irradiation. 74 Except for these differences, the results from HSE0.15 and LDA+GW 38 show similar trends overall.…”
Section: B Silicon Vacancy-type Defectssupporting
confidence: 75%
“…Kerbiriou et al also examined the sample using electron paramagnetic resonance (EPR) and identified the T1 signal, attributed to V 1− Si (see Ref. [56][57][58][59]. Considering the calculations results presented here, we firstly verified whether the defect corresponding to the experimental lifetime could be the silicon vacancy changing its charge state.…”
Section: Comparison With Experimentssupporting
confidence: 54%
“…The V Si defect EPR signal has been found in 4H‐SiC and 6H‐SiC . A silicon‐vacancy related defect identified in 3C‐SiC n‐doped with a diamagnetic ground state and a paramagnetic triplet excited state has also been observed via EPR . In 4H‐SiC VSi has two PL lines stable up to 500–600 °C associated with two charge states (Figure (c)).…”
Section: Optical Defects In Sicmentioning
confidence: 72%